Protoplast fusion between Pleurotus opuntiae and Pleurotus cystidiosus - Krishnapriya, P J; Geetha, D (Mushroom Research, 2020)
Vanillin (0.05 %) and carbendazim (1 mM) were selected as dual biochemical markers for the PEG mediated protoplast fusion between Pleurotus opuntiae and P. cystidiosus. Three days old P. cystidiosus and four days old P. opuntiae recorded the maximum protoplast yield at five and four hours after incubation, respectively with 0.6 MKCl and 30 mg ml-1 of enzyme consortium. Eight fusant lines with varied mycelial characters were obtained. Among fusants, F6 and F8 did not segregate in the second generation whereas, F4 segregated. F6 and F8 recorded higher biological efficiency of 168.05 and99.95 per cent respectively compared to the parental lines and other fusants. Sporocarp of F6 and F8 were morphologically similar to P. cystidiosus and P. opuntiae respectively; and F8 also exhibited low temperature adaptability.